الشذوذ الجنسي بين الشريعة الإسلامية والقانون الدولي لحقوق الإنسان : دراسة مقارنة - Ragab Mohamed Ahmed Ragab (Universitas Islam Indonesia, 2022)
This research “Homosexuality between Islamic Sharia and International Human Rights Law” A Comparative Study, presented as one of the conditions for obtaining a PhD in Islamic Law - Faculty of Islamic Studies - at the Islamic University of Indonesia - Yogyakarta, and it is a library research. The data collected and mentioned by the researcher are published on the scientific arena in books, research,scientific journals and official statements. The researcher followed the scientific method in research work, taking into account the scientific accuracy in the ratio of the sayings of their authors, and mentioning the references in the footnote. Because homosexuality has become the focus of international institutions, and many conferences have been held regarding it, on its legality and the possibility of its permissibility in Islamic Sharia and international law; This research was, and it included four intertwined topics: (1) the terms of homosexuality, its scientific reference and its harms (2) His ruling in Islamic law and the principles of governance, and its ruling in the most famous religions, and the Muslim’s position on homosexuality in the countries in which he lives (3) and his ruling in International law and its premises (4) international law and the cultural specificity of peoples. This research ends with several results, the most important of which are: The need to control terminology and the necessity to use them correctly is one of the most important rules in scientific research, especially if the term touches the core of the intellectual and moral characteristics of the nation, and is used in more than one sense. , including the term homosexuality. So the correct terminology for all illicit sexuality practices is the term